APPLICATION OF FORENSIC ACCOUNTING TECHNIQUES AS ANTIDOTE FOR CURBING FRAUD IN NIGERIA BUDGET IMPLEMENTATION ADEGBIE - Folajimi Festus*, DADA Samuel Olajide, OWOEYE Kehinde & SIYANBOLA Tunji Trimisu (International Journal of Research Science and Management, 2020)
Budgeting is a fiscal policy used by the government to grow and develop the economy to ensure performance, stability and sustainability. Studies have shown that diversion of budgeted allocated funds, misappropriation of funds, fraud and uncompleted capital and developmental projects are major challenges facing budgetary system in Nigeria public sector. Studies further revealed that various strategies used to resolve the problem have not been successful. This study evaluated the impact of the applying forensic accounting techniques in curbing fraud in Nigeria budget implementation. The study employed survey cross-sectional research design. The population consisted of 195 staff of federal government establishments connected with budgetary system and fiscal policy. With the use of total enumeration, 195 copies of the questionnaire were administered with a retrieval rate of 150 copies (77%).The study adopted descriptive and inferential statistics to analyze the data. The findings showed that Investigative and Audit Support Service have strong impact on fraud and misappropriation of budgeted allocation funds β=0.342,F (1,149)=10.587,p-value=.002.The result also showed that Investigative and Audit Support Service has significant impact on uncompleted capital and developmental projects.β=0.745,F(1,149)=249.621,p-value=.003.The study concluded that the application of forensic accounting techniques have positive effect on curbing fraud in budget implementation. The study recommended that the federal government should make a policy to incorporate forensic accounting in Nigeria budgetary system